Compostos voláteis como sedativos, anestésicos e antinociceptivos em peixes - Rodrigues, Patricia (2020)
Natural products are a drug discovery source for both humans and veterinary treatment. Consequently, in the last decade, essential oils have been researched as fish anesthetics and sedatives, however, there are a small number of antinociceptive drug development studies using fish as an animal model. Also, the essential oils use is limited in pisciculture maybe due to the physicochemical limitations, such as high hydrophobicity. Thus, nanotechnology can protect and facilitate these compounds dispersion in water. Therefore, through this dissertation, it is expected to improve the volatile compounds use as anesthetic and sedative agents, even as increase the antinociceptive use as well-being promoters for fish. Firstly, silver catfish (Rhamdia quelen) nociceptive method was standardized with acetic acid 15 % (3μL), formalin 1 % (10 μL) and menthol 0.5 % (1 μL) administered in the lips. Additionally, due to the Nectandra grandiflora essential oil anesthetic/sedative activity, it was suggested to evaluate the antinociceptive activity, as well as linalool. In addition, we developed a N. grandiflora essential oil nanoemulsion formulation (NEN), and evaluate the anesthetic, sedative and toxicity by immersion bath in Nile tilapia (Oreochromis niloticus) compared with the free essential oil (FEO). Chemical analyses were performed by gas chromatography coupled to mass spectrometry and flame ionization detector. Among the results, to induce the nociceptive-like behavior in silver catfish we used 15 % acetic acid (3 μL), 1 % formalin (10 μL) and 0.5 % menthol (1 μL). Nociceptive-like behavior was verified in ten locomotor parameters that were reversed with intramuscular morphine (5 mg/kg) injection, and this antinociceptive activity was antagonized by naloxone (5 mg/kg). However, only acetic acid-induced the nociceptive-like behavior at the maximum speed parameter. Given this, the volatile compounds treatment was performed only against acetic acid and the N. grandiflora essential oil (10 mg/kg) had low activity. Linalool (50 mg/kg), on the other hand, has strong antinociceptive activity by reversing all locomotors parameters, with a related mechanism to opioid receptors. Secondarily, through the spontaneous emulsification process, we developed thirteen NEN and the nanoemulsification process protected the oil chemical composition for 60 days and reduced the FEO side effects. Therefore, the NEN 100 mg/L concentration for anesthetic and 30 mg/L for sedation application are safe. Thus, FEO depressant activity was improved and also refined for tilapia. Moreover, the two fish species use covers not only nociceptive-like behavior in an unknown species but also a new O. niloticus pharmacological alternative for sedation and anesthesia. Consequently, the silver catfish new nociception experimental model proposed demonstrated specificity, since the nociceptive-like behavior was reverted by linalool and morphine, which have described analgesic activity. Briefly, this dissertation contributes to research that aims to combine volatile compound and nanotechnological knowledge into an effective and safe anesthetic drug development.